Desire of Death in Sadiq Hidayat,s Selected Short Stories: صادق ہدایت کے منتخب افسانوں میں خواہشِ مرگ (DARYAFT, 2023)
Sadiq Hidayat is renown Persian writer. He is one of the few Iranian Persian writers whose many fictions have been translated into Urdu. He introduced modern techniques in Persian fiction. In some of his stories Sadiq Hidayat has presented the subject of death from different angles. somewhere in the human being there is a desire to escape from his problems in the death. This desire of death can be found in some of his short stories because he also committed suicide by suffocating poison gas on April 9, 1951 in Paris. This research article is based on an effort to find different aspects of sadness and sensitivity in his Urdu translated short stories. He has skillfully made the individual and collective problems and psychological confusions of people in his fiction. He also tried to reflect the lives of depressed people and their emotional downfalls. In his fiction there is a noticeable deep observation of marital attitudes depression۔ He has also mentioned the life of animals and their death. The death, as solution of problems can be seen especially in his stories. This is an analytical research study, based on Urdu translations of his fiction. We can observe that death; especially suicide is very favorite subject of his characters.
Keywords: Depression; Attraction of death; Persian fiction of Sadiq Hidayat